2015
DOI: 10.1111/caim.12114
|View full text |Cite
|
Sign up to set email alerts
|

Business Model Design Games: Rules and Procedures to Challenge Assumptions and Elicit Surprises

Abstract: Previously well‐established companies are currently struggling to secure profits, mainly due to the pressure from new communication technology‐based business models. Because of this, the business model research field has flourished in recent years, but most of the applied approaches still rely on linear, rational conceptions and causal reasoning. Through three games and three business cases, it is argued that experimental game‐like innovation activities can lead the way into another approach to business model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 27 publications
0
17
0
1
Order By: Relevance
“…Based on a comprehensive review of the current literature a definitional corridor explaining the BGs international nature can be derived as follows: At least four foreign markets have to be conqueredthese markets have to dispose of a high psychic, cultural and geographic distance Oviatt and McDougall (1994);McAuley (1999); Zahra et al (2000); Moen (2002); Andersson and Wictor (2003); Bell et al (2003); Knight and Cavusgil (2004); Laanti et al (2007); Kuivalainen et al (2012) Moreover, researchers have observed that many BGs are forced into globalization because of their high specialized products (Trkman et al, 2015) and that their export performance depends on innovations: the more a firm innovates the more innovations will be exported (Pels and Kidd, 2015). As reflection of the business model their product differentiation strategy influences positively the internationalization process (Gudiksen, 2015) and technological intensity as well as RandD intensity, representing the BGs international innovativeness, are significantly associated with export performance (Amshoff et al, 2015;Dhanaraj and Beamish, 2003).…”
Section: International Performance Of Bgsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on a comprehensive review of the current literature a definitional corridor explaining the BGs international nature can be derived as follows: At least four foreign markets have to be conqueredthese markets have to dispose of a high psychic, cultural and geographic distance Oviatt and McDougall (1994);McAuley (1999); Zahra et al (2000); Moen (2002); Andersson and Wictor (2003); Bell et al (2003); Knight and Cavusgil (2004); Laanti et al (2007); Kuivalainen et al (2012) Moreover, researchers have observed that many BGs are forced into globalization because of their high specialized products (Trkman et al, 2015) and that their export performance depends on innovations: the more a firm innovates the more innovations will be exported (Pels and Kidd, 2015). As reflection of the business model their product differentiation strategy influences positively the internationalization process (Gudiksen, 2015) and technological intensity as well as RandD intensity, representing the BGs international innovativeness, are significantly associated with export performance (Amshoff et al, 2015;Dhanaraj and Beamish, 2003).…”
Section: International Performance Of Bgsmentioning
confidence: 99%
“…Based on their product differentiation strategy which gets reflected in their business models they achieve a higher export performance the more they innovate (Gudiksen, 2015;Pels and Kidd, 2015). In a broader view, future research can orientate on the BG business model archetype with its components presented in the propositions (e.g., market, capability factors) to have a guiding map for research.…”
Section: Practical and Theoretical Implicationsmentioning
confidence: 99%
“…The approach of "tangible business modelling" allowed participants to "express themselves with their hands" [21]. The analyzed literature reported the use of tangible resources such as sticky notes [25] or balls and bricks [32] to facilitate collaboration among (multi-disciplinary) BM co-creation teams. Buur and Gudiksen conducted iterative BM experiments in various interactive settings to trigger new discussions and solution-based thinking.…”
Section: Design Thinkingmentioning
confidence: 99%
“…The researchers arrived at the conclusion that "playfully 'thinking with hands and body' enhances 'the quality of conversations' towards an innovative outcome" [21]. Similarly, Gudiksen chose different BM design games for the playful experimentation with new BM ideas [32]. It has been demonstrated that approaching the BM as a design problem advances new perspectives on BMI initiatives.…”
Section: Design Thinkingmentioning
confidence: 99%
See 1 more Smart Citation